An analysis of goal scoring patterns during the 2010 FIFA World Cup - Seaton, M. A.; Leventer, L. (World Congress of Performance Analysis of Sport IX, 2012)
The aim of the present study is to describe the characteristics of goal scoring patterns at the 2010 FIFA World Cup. All goals (n = 145) excluding penalties were analysed by a computerized notation system. Inter and intra observed reliability was calculated with the Kappa statistic. Chi-square and cross-tabulation methods were used for the data analysis and the level of significant was set at p<0.05. Inter and mean intra-observer reliability was 0.91 and 0.88 respectively. A uniform distribution of goals through the 15min time intervals was not observed, as significantly more goals were scored in the later part of each match half`s (Chi² = 49.3, df = 7, p<0.001). This resulted in more goals being scored in the second half compared to the first half of the match 58% to 42%, (p=0.06). As expected significantly more of goals were scored by strikers (51.5%), while midfielders and defenders scored 35.5% and 13% respectively (Chi² = 30.1, df = 2, p<0.001). During the first half of games defenders scored significant more goals (80%) from headers (30%, Chi² = 16.3, df = 2, p<0.001). In addition more goals were scored from headers inside the six yard box at stage two of the tournament (60%) compared to the group stage (29%). Goals from organized offense pattern of play (60%) were significantly (Chi² = 44.0, df = 2, p<0.001) the most frequent compared to counter-attack and set-pieces 15% and 25% respectively. Most goals had been scored from a combination play (58%), while individual action resulted in 47% of goals (Chi² = 40.0, df = 2, p<0.001). Significantly more goals were scored from inside the penalty area (Chi² = 25.6, df = 2, p<0.001) 54% compared to inside the 6 yard box 25% and outside the penalty area 21%. Analysis of goals from set-piece show that the majority were scored from free-kicks (50%), compared to corners (38%) and throw-ins (12%; Chi² = 7.8, df = 2, p<0.05). Slightly more of these were scored during the first half, but this was not significant. These results follow the expected patterns of previous World Cups analysis (Acar et al., 2007; Armatas, Yiannakos, & Sileloglou, 2007) especially with regards to the increased probability of a goal being scored the match progresses. As these authors stated justification come from fatigue, possibly exasperated at this tournament due to games being played at altitude, which lead to reduced capacity for players to repeat high intensity work, thereby reducing work rates and increasing lapses in concentration, which consequently lead to goals being scored.